On the genus Neoscotolemon (Opiliones: Laniatores: Samooidea incertae sedis) with the description of one new species - Pérez-González, Abel; Mamani, Vanesa; Proud, Daniel N. (Zootaxa, 2025)
The genus Neoscotolemon Roewer, 1912, is herein reviewed and re-diagnosed for the first time using modern taxonomic standards. Neoscotolemon is removed from Grassatores incertae sedis and transferred to the superfamily Samooidea incertae sedis, transl. nov. The genera Citranus Goodnight & Goodnight, 1942, Rula Goodnight & Goodnight, 1942, and Vlachiolus Šilhavý, 1979, are considered new subjective synonyms of Neoscotolemon Roewer, 1912. Neoscotolemon pictipes (Banks, 1908) is redescribed and fully illustrated, including, for the first time, the external and genital morphology of males. Neoscotolemon armasi spec. nov. is described from Isla de la Juventud, Cuba. Five additional species are transferred to Neoscotolemon, including some that were newly ranked from subspecies to species: Neoscotolemon bolivari (Goodnight & Goodnight, 1945) comb. nov., stat. rest. (transferred from Stygnomma), N. cotilla (Goodnight & Goodnight, 1945) comb. nov., nom. rest., stat. rest. (transferred from Stygnomma), N. spinifer (Packard, 1888) comb. rest. (transferred from Stygnomma), N. tancahensis (Goodnight & Goodnight, 1951) comb. nov., stat. prom. (transferred from Stygnomma), and N. vojtechi (Šilhavý, 1979) comb. nov. (transferred from Vlachiolus). Finally, upon reexamination of Neoscotolemon lutzi Goodnight & Goodnight, 1942, the male genital morphology, herein illustrated for the first time, indicates that this species is not related to Neoscotolemon and is therefore transferred to Metapellobunus and combined as Metapellobunus lutzi (Goodnight & Goodnight, 1942) comb. nov. A map is provided showing the known distribution of Neoscotolemon in the southeastern USA, Cuba, Mexico, and Belize with doubtful and unconfirmed records in Jamaica and Cayman Islands. Neoscotolemon is characterized by multiple somatic and genitalic traits. Atop the hourglass-shaped scutum magnum, there is a widely-separated pair of eyes with a large spiniform apophysis placed between them. The pedipalps are robust, and in major males they are elongated and thickened. In major and minor males, the metatarsus III is enlarged, ventrally covered with modified trichomes, and possesses aggregated pores distally. The penis has a ventral plate ending in a deep calyx, armed with two bilateral rows of macrosetae, and a short, pointed stylus that is basally fused to two laminar conductors. Although the family allocation remains uncertain, the re-diagnosis of Neoscotolemon, together with the re-description of the type species, makes this an easily recognizable genus, among Samooidea, that now contains seven species.